TouchDevelop – Programming Cloud-Connected Mobile Devices via Touchscreen - Moskal, Michal; Tillmann, Nikolai; Fahndrich, Manuel; Halleux, Jonathan "Peli" de (Microsoft Technical Report, 2011)
The world is experiencing a technology shift. In 2011, more touchscreen-based mobile devices like smartphones and tablets will be sold than desktops, laptops, and netbooks combined. In fact, in many cases incredibly powerful and easy-to-use smart phones are going to be the first and, in less developed countries, possibly the only computing devices which virtually all people will own, and carry with them at all times. Furthermore, mobile devices do not only have touchscreens, but they are also equipped with a multitude of sensors, such as location information and acceleration, and they are always connected to the cloud. TouchDevelop is a novel application creation environment for anyone to script their smartphones anywhere – you do not need a separate PC. TouchDevelop allows you to develop mobile device applications that can access your data, your media, your sensors and allows using cloud services including storage, computing, and social networks. TouchDevelop targets students, and hobbyists, not necessarily the professional developer. Typical TouchDevelop applications are written for fun, or for personalizing the phone. TouchDevelop's typed, structured programming language is built around the idea of only using a touchscreen as the input device to author code. It has built-in primitives which make it easy to access the rich sensor data available on a mobile device. In our vision, the state of the program is automatically distributed between mobile clients and the cloud, with automatic synchronization of data and execution between clients and cloud, liberating the programmer from worrying (or even having to know about) the details. We report on our experience with our first prototype implementation for the Windows Phone 7 platform, which already realizes a large portion of our vision. It is available on the Windows Phone Marketplace.